Aerial Fire Suppression to Combat Forest Fire – A Case Study from Parambikulam Tiger Reserve - Anjan Kumar, B. N. (Indian Forester, 2019)
Forest fire management is gaining more significance over the passage of time. Aerial forest fire suppression is the use of aircraft and other aerial resources to combat forest fires. In India, the usage of aircrafts for aerial forest fire suppression operation is very rudimentary in comparison to the countries like USA, Australia, Russia, Turkey, etc. In this case study, the technical aspects involved in aerial fire suppression using MI-17 helicopter of Indian Air Force and the intricacies in organizing and execution of this aerial forest fire suppression operation is discussed. Various aspects of the aerial forest fire suppression like type of air craft, mechanism of fire suppression, response time and execution mechanism are assessed by analyzing field observations during the operation carried out in Parambikulam Tiger Reserve.